Navigating Stigma and Discrimination: Betrothal Challenges Faced by Descendants of Leprosy in Madura, Indonesia - Sabri, Fahruddin Ali; Rosyadi, Imron; Isfironi, Mohammad; Hadi, Mukhammad Nur; Sulthon, M; Khazin, A. Mufti (Institut Agama Islam Negeri Curup, 2023)
This article aims to uncover stereotypes against lepers and their descendants by impacting difficulties in finding a potential partner and the risk of being abandoned by a potential partner. This clearly cannot be underestimated and is part of the State and non-state actors’ responsibilities in protecting human rights based on Islamic law. This article used ethnography as a methodology of research when dialogue and observation were used as research techniques. This study’s findings revealed that the descendants of lepers were considered a threat to the survival of their descendants, so they got discriminatory treatment, exclusion, stigmatization, exile, and inequality which in turn could interfere with their dignity. The Dhohiri School had a different view out of the four Schools of Islamic law namely Hanafi, Maliki, Shafi'i, and Hanbali, where this School rejected divorce because of disability in any form. Dhohiri School had shown partiality and respect for the human rights of lepers and their descendants to engage in Betrothal and marriage without any discrimination, exclusion, stigmatization, banishment, or inequality of any kind. The alignment of the Dhohiri School is in line with the State and non-state actors’ efforts to minimize the inhumane and terrible treatments of people with leprosy and their descendants.